Artistic and Aesthetic Skills of Primary Class Students (Journal of Pedagogical Inventions and Practices, 2023)
In this article, it is mentioned about the abilities that are developed in elementary school students from the kindergarten period to the period of primary education. They talk about how the artistic-aesthetic process develops.